Linguistic And Cultural Paradigm of the Hero of French and Russian Folk Tales - Norova Mokhitobon Fayzulloevna (Zien Journals, 2022)
This article deals with the linguistic and cultural paradigm of the hero of French and Russian folk tales. It also discusses research by foreign and Russian scholars, as well as the features of French and Russian fairy tales.
Keywords: Phraseologisms; term; fairy tale; folklore